Investigation of radial distribution of atomic hydrogen flux to the plasma facing components in steady state discharges in QUEST tokamak. (March 2021) - Kuzmin, A.; Kobayashi, M.; Hanada, K.; Idei, H.; Onchi, T.; Mori, S.; Yoneda, N.; Shikama, T.; Hasuo, M.; Ido, T.; Nagashima, Y.; Ikezoe, R.; et al.
Highlights: Atomic hydrogen flux to the plasma facing materials plays important role in fusion devices. Reciprocate permeation probe allows to measure the hydrogen flux directly, in-situ, at several radial positions. Radial distribution of hydrogen flux in long duration inboard limiter configuration discharges is investigated. The atomic flux behind the PFCs drops to 6 Abstract: To study radial distribution of hydrogen flux in peripheral plasma in long duration tokamak discharges, permeation and Langmuir reciprocate probes are used. The atomic hydrogen flux to the walls at several radial positions is deduced from the permeation flux. Contribution of the ions to the hydrogen flow is deduced from the Langmuir probe ion saturation current. It is found, that the atomic hydrogen has the most contribution to the hydrogen flow behind the plasma facing components (PFCs), while the ion flux there is negligible. The atomic flux behind the PFCs drops to the value of F 4.3 × 10 15 H / m 2 / s, which is 6 % of that just in front of PFCs, F 7.7 × 10 16 H / m 2 / s .